2021
DOI: 10.1002/kjm2.12388
|View full text |Cite
|
Sign up to set email alerts
|

The effects and mechanism of α‐mangostin on chemosensitivity of gastric cancer cells

Abstract: This work investigated the effect of α-mangostin (α-M) on gastric cancer (GC) cell chemoresistance and its underlying mechanisms. Different concentrations of α-M and CDDP were applied to treat GC cells (SGC7901) and CDDP-resistant GC cells (SGC7901/CDDP) for 24 or 48 h. CCK-8 assays were used to measure the inhibitory effect of CDDP or α-M on SGC7901 and SGC7901/CDDP cells as well as the halfmaximal inhibitory concentrations (IC50) of α-M for SGC7901 and SGC7901/CDDP cells. The optimal concentration and induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Given the regulatory role of autophagy in the anti-tumor and anti-inflammatory effects of α-MG ( 31 , 32 ), we examined the expression levels of autophagic proteins in PSCs after drug stimulation in terms of time and concentration, respectively. In addition to the temporal dosage effect, by fluorescence localization, we found that autophagic proteins were aggregated on the envelopes of PSCs and partially expressed on the suckers, which could reduce larval defense against the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Given the regulatory role of autophagy in the anti-tumor and anti-inflammatory effects of α-MG ( 31 , 32 ), we examined the expression levels of autophagic proteins in PSCs after drug stimulation in terms of time and concentration, respectively. In addition to the temporal dosage effect, by fluorescence localization, we found that autophagic proteins were aggregated on the envelopes of PSCs and partially expressed on the suckers, which could reduce larval defense against the environment.…”
Section: Discussionmentioning
confidence: 99%
“… Zhang et al (2019) indicated that protocatechuic acid reduces the dosage of 5-fluorouracil and enhances the chemosensitivity of GC cells to 5-fluorouracil ( Motamedi et al, 2020 ). It is reported that α-mangostin increases the chemosensitivity of GC cells to cisplatin by inactivating the EBI3/STAT3 pathway ( Li and Zeng, 2021 ). These data of Zhang et al (2019) demonstrated that piperlongumine potentiates the effect of chemotherapy of oxaliplatin in GC cells.…”
Section: Effects Of Phytochemicals On the Occurrence And Development ...mentioning
confidence: 99%
“…Evidence indicates that α-mangosteen (AM) inhibits various cancer cell lines [ 14 , 19 , 20 ]. The present study shows that the rate of tumorigenicity of LA7 cells in these rats was 80%, the body weight was decreased, and the tumor volume was statistically increased ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%